1999
DOI: 10.1086/515126
|View full text |Cite
|
Sign up to set email alerts
|

Should Prophylaxis for Pneumocystis carinii Pneumonia in Solid Organ Transplant Recipients Ever Be Discontinued?

Abstract: Solid organ transplant recipients are at risk for Pneumocystis carinii pneumonia (PCP), but the risk of PCP beyond 1 year is poorly defined. We identified 25 cases of PCP in 1,299 patients undergoing solid organ transplantation between 1987 and 1996 at The Cleveland Clinic Foundation (4.8 cases per 1,000 person transplant-years [PTY]). Ten (36%) of 28 PCP cases (transplantation was performed before 1987 in three cases) occurred > or = 1 year after transplantation, and no patient developed PCP while receiving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
2
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 34 publications
6
127
2
3
Order By: Relevance
“…Currently, because of universal prophylaxis during the first 6-12 months after transplantation, this infection is now rare and the overall incidence rate of P. jiroveci pneumonia (PCP) in kidney transplant recipients is 0.8 case per 1000 person after completion of 1 year of prophylaxis (88). PCP is associated with a 29%-50% mortality rate in kidney transplant recipients (89).…”
Section: P Jiroveci Infectionmentioning
confidence: 99%
“…Currently, because of universal prophylaxis during the first 6-12 months after transplantation, this infection is now rare and the overall incidence rate of P. jiroveci pneumonia (PCP) in kidney transplant recipients is 0.8 case per 1000 person after completion of 1 year of prophylaxis (88). PCP is associated with a 29%-50% mortality rate in kidney transplant recipients (89).…”
Section: P Jiroveci Infectionmentioning
confidence: 99%
“…7 Pneumocystis jiroveci mortality in RTRs is high despite aggressive treatment, and it has been reported to be between 27% and 50%. 3,8 To improve outcomes of RTRs, previous studies have identified PJP risk factors in RTRs including poor renal function, prior allograft rejection, mycophenolate mofetil use, and persistent lymphocytopenia. [9][10][11] Moreover, to reduce PJP mortality rate in RTRs, it is crucial to identify determinants of PJP mortality that have not been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…It may occur either as sporadic cases or as outbreaks 1,6 . It may be prevented by the prophylactic use of trimethoprim-sulfamethoxazole (TMS) 2,4 .…”
Section: Introductionmentioning
confidence: 99%